Analisis Kelayakan Investasi Penggemukan Sapi Bali di Kabupaten Konawe Selatan - Nur, Nurholis; Tuwo, Muhammad Akib; Hafid, Harapin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
This research aims to determine the number of investment expenses and analyze the technical and financial feasibility fattening Bali cattle in South Konawe. research conducted in November of 2009. Data analyzed by (1) Net Present Value (NPV), (2) Internal Rate of Return (IRR), (3) Net Benefit Cost Ratio (NBCR), (4) Sensitivity Analysis. Based on research results can be concluded : (1). south Konawe technically possible to host the fattening of Bali cattle, because conditions in accordance with technical requirements cultivation and cultivation of grass feed beef cattle, (2) the cost of fish per year investment in 1200 amounted to Rp 3,029,547,500 which is used to open the garden 4.5 hectares of grass, grass seeds king grass, build a cow shed, office buildings, warehouses, supporting infrastructure, and machinery and equipment, (3) The financial analysis showed that fattening Bali cattle in South Konawe feasible with NPV Rp 7,678,359,025, IRR of 44.20% and NBCR Rp 3.09 (4) results of sensitivity analysis showed that fattening Bali cattle in South Konawe remain viable despite a 10% increase in costs or decrease benefits by 10%, and (5) fattening Bali cattle in South Konawe Regency positive impact that can not be measured with money that is: improvement of soil fertility, labor absorption, and increased knowledge to farmers on how to properly cultivate Bali cattle.